Recent advances to accelerate re-endothelialization for vascular stents - Bedair, Tarek M.; ElNaggar, Mahmoud A.; Joung, Yoon Ki; Han, Dong Keun (SAGE-Hindawi Access to Research, 2017)
Cardiovascular diseases are considered as one of the serious diseases that leads to the death of millions of people all over the world. Stent implantation has been approved as an easy and promising way to treat cardiovascular diseases. However, in-stent restenosis and thrombosis remain serious problems after stent implantation. It was demonstrated in a large body of previously published literature that endothelium impairment represents a major factor for restenosis. This discovery became the driving force for many studies trying to achieve an optimized methodology for accelerated re-endothelialization to prevent restenosis. Thus, in this review, we summarize the different methodologies opted to achieve re-endothelialization, such as, but not limited to, manipulation of surface chemistry and surface topography.